Incorporation of palm oil polyol in shape memory polyurethane: Implication for development of cardiovascular stent - Ahmad Zubir S.; Mat Saad N.; Harun F.W.; Ali E.S.; Ahmad S. (John Wiley and Sons Ltd, 2024)
Shape memory polyurethanes (SMPU) are one of the advanced materials that have potential applications in the field of biomedical particularly vascular stent. This paper studies the effect of incorporating palm oil polyol (POP) up to 40% molar ratio in place of petroleum-based polyol in the preparation of SMPU due to environmental concern. Polycaprolactone diol was utilized as the soft segment while 4,4?-diphenylmethane diisocyanate and 1,4-butanediol as the hard segments. The SMPU was prepared using two-step prepolymer method, and the fabricated samples were characterized to study the effect of POP on the thermal properties, tensile, and shape memory behavior of polyurethane. The results obtained have shown that SMPU with incorporation of POP showed good shape fixity (100%) and elongation at break (245%) up to 20% molar ratio of POP. The presence of dangling chains of fatty acid in POP was believed to enhance the flexibility of SMPU molecular chains by acting as a plasticizer. On the other hand, the shape recovery of SMPU remains high even at 40% molar ratio of POP, and the thermal stability of SMPU increased with the addition of POP. It is proposed that the synthesized POP-based SMPU is a suitable candidate for cardiovascular stent as they possessed desired thermal, mechanical, and shape memory properties. 2018 John Wiley & Sons, Ltd.